Mycotoxins revisited: Part II - Berger, Kyan J.; Guss, David A. (The Journal of emergency medicine, 2005)
Mushrooms are ubiquitous in nature. They are an important source of nutrition, however, certain varieties contain chemicals that can be highly toxic to humans. Industrially cultivated mushrooms are historically very safe, whereas foraging for mushrooms or accidental ingestion of mushrooms in the environment can result in serious illness and death. The emergency department is the most common site of presentation for patients suffering from acute mushroom poisoning. Although recognition can be facilitated by identification of a characteristic toxidrome, the presenting manifestations can be variable and have considerable overlap with more common and generally benign clinical syndromes. The goal of this two-part article is to review the knowledge base on this subject and provide information that will assist the clinician in the early consideration, diagnosis and treatment of mushroom poisoning. Part I reviewed the epidemiology and demographics of mushroom poisoning, the physical characteristics of the most toxic varieties, the classification of the toxic species, and presented an overview of the cyclopeptide-containing mushroom class. Part II is focused on the presentation of the other classes of toxic mushrooms along with an up-to-date review of the most recently identified poisonous varieties.